Removal of Fluoride from Aqueous Solution by Adsorption onto Attapulgite Supported CeO2 Nanoparticles - Wang, Jiahong; Chang, E.; Ji, Yanfen (Asian Journal of Chemistry, 2015)
Attapulgite supported CeO2 (ATP-CeO2) was prepared and characterized by FTIR, XRD, TEM and zeta potential measurement. ATP-CeO2 exhibits high adsorption capacity for aqueous fluoride and fluoride adsorption amount onto ATP-CeO2 decreased with rise in solution pH and electrostatic interaction and anionic exchange may contribute to the enhanced fluoride adsorption. The presence of anions in solution suppressed fluoride adsorption by competing with fluoride ions for the active sites of the adsorbent surface. Adsorption isotherms of fluoride can be well described by Langmiur model and the maximum adsorption amount were 14.97, 18.08 and 22.42 mg/g at 15, 25 and 35 °C, respectively and fluoride adsorption onto ATP-CeO2 increased with increasing adsorption temperature, indicating of an endothermic process. Pseudo-second order kinetic equation can fit the fluoride adsorption satisfactorily. Fluoride saturated ATP-CeO2 can be easily desorbed in 0.1 mol/L NaOH solution and regenerated adsorbents still showed high adsorption amount for fluoride in water.